MyLogger: fast logging with HyLogger spectral mineralogy - J. M. Stromberg; C. Laukamp; E. J. Hill; A. Rodger (Australian Journal of Earth Sciences, 2026)

Analysing the structure of antibodies using circular dichroism with an antibody augmented reference set and the algorithm SELCON - Søren Vrønning Hoffmann; Maria G. Bruque; Nykola C. Jones; Alison Rodger; Jean Aucamp; Tim R. Dafforn; Owen R. T. Thomas (European Biophysics Journal, 2026)

Evaluating the evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards - Jason J. Kolbe; Jacob D. Ward; C. Mike Norris; John Rodgers; Sydney Wayne; Daniel A. Warner (Evolutionary Ecology, 2026)
Whether phenotypic plasticity facilitates adaptive evolution is a key question in evolutionary ecology. The discovery of limb-length plasticity in two Anolis lizard species led to hypotheses about its role in the Anolis radiation. Yet, whether limb plasticity is realized in nature and has adaptive significance is poorly understood. In this study, we combined a limb-length plasticity experiment, lab-based assays of hatchling behavior, and field-based measures of individual perch-diameter use of hatchling A. sagrei . We compared our findings to previous lab experiments and field studies to better understand the ecological conditions that might elicit limb plasticity and influence the adaptive potential of limb-length in Anolis lizards. Results from our lab experiment did not support limb-length plasticity. Significant limb-length differences due to plasticity were found in some previous experiments but not others. Intriguingly, repeated observations of individual hatchlings at night revealed consistent use of narrow-diameter perches for an island population. In contrast, individual diurnal perch-diameter use in adult A. sagrei was much less uniform. Little evidence exists for adaptive behavior or performance in hatchlings related to limb length and perch diameters. Several aspects of anole behavior and ecology, such as perch preferences and sleep-site use, influence perch-diameter use. Differences among populations in hindlimb length for Bahamian islands often exceed the average plastic response found in lab experiments. Evidence for the ecological relevance and adaptive potential of limb-length plasticity in Anolis lizards is currently mixed. A better understanding of how perch-diameter use results in biomechanical and developmental cues that influence limb growth is needed. The lack of clear support from lab and field studies urges caution when hypothesizing about the role of limb-length plasticity in the Anolis radiation.

Inshore marine coastal zone migration patterns in Atlantic salmon post‐smolts emigrating from eight rivers in north‐east Scotland - Colin E. Adams; Ruaidhri Forrester; Matthew Newton; Angus J. Lothian; Hannele M. Honkanen; Davide Thambithurai; Lorna Wilkie; Melanie A. Smith; Marcus Walters; Richard Miller; Karen Muller; Brian Shaw; et al. (Journal of Fish Biology, 2026)
Atlantic salmon, Salmo salar , migrate through multiple habitat types, each having the potential to impact differently upon migration success. The inshore marine coastal zone is arguably disproportionately impacted by potential stressors on populations. We investigated the migration of Atlantic salmon post‐smolts ( n = 898) from eight rivers (populations) through the inshore marine coastal zone over a 2‐year period using acoustic telemetry. Migration success through marine inlets where fish first entered seawater, and through the wider inshore marine coastal area (the Moray Firth, north‐east Scotland) was consistently high across populations and across years (mean = 77%). There was no evidence of the high inshore marine predation rates reported elsewhere. Post‐smolts utilised well‐defined inshore marine migration pathways that were broadly consistent among populations and over time. The pace of migration through the inshore marine coastal habitat was also consistently rapid across populations and time, with the period of migration being seasonally constrained (mean across population = 36.5; range 18–45 days). Taken together with existing literature, this study suggests that the patterns of migration of Atlantic salmon post‐smolts through the inshore marine coastal zone are likely highly environment specific.

Future actions for the ocean acidification research community to support marine industries and coastal communities of Aotearoa New Zealand - Rachel Hale; Lea Muetzel; Jessica Ericson; Joanna Copedo; Vonda Cummings; Norman L. C. Ragg; Christina McGraw; Kim Currie; Kirsten Rodgers; Mary A. Sewell (New Zealand Journal of Marine and Freshwater Research, 2025)
Increasing atmospheric CO 2 emissions are altering the carbonate chemistry of seawater in a process known as ocean acidification (OA). This is a growing issue for marine industries and communities. During the 2023 New Zealand Ocean Acidification Community (NZOAC) Conference, the community undertook a horizon scanning exercise to determine potential future activities and opportunities. Conference participants were sent questions that focussed on topics of importance to the Aotearoa New Zealand and global OA community. Sixteen potential actions were identified. During the conference, participants voted for actions they perceived to be most important to give each an overall priority score. In order, the five top priority actions were to (i) re‐engage with policymakers to ensure OA is included in policies around climate change, oceans, fisheries, and education; (ii) maintain funding for current observation platforms; (iii) focus on solutions during engagement actions; (iv) obtain funding for new OA focused research; and (v) engage more with the public through community/public participatory science. We summarise the activities identified to address these actions and discuss potential ways forward for the NZOAC and wider research community to undertake the required research and provide much needed guidance to underpin OA mitigation and adaptation efforts.

Variation in estimates of the footprint of large, ground-mounted photovoltaic solar energy in the United States and its associated land-cover change across three datasets - Michael O. Levin; Emma Forester; Elizabeth L. Kalies; Lauren Goodman; Jason S. Hagani; Chevon C. Holmes; Noah Z. Krasner; Caitlin Markus; Jared B. Meek; Anubhav Vanamamalai; Shivani Agarwal; Uzma Ashraf; et al. (Journal of Environmental Management, 2025)

Hydrogen, single-carbon compounds, and thermal regime in the oceanic ultramafic-dominated lithosphere: insights from a deep borehole on the Atlantis Massif - Susan Q. Lang; C. Geoffrey Wheat; Kristin L. Dickerson; Mark K. Reagan; Ivan P. Savov; Jordyn A. Robare; William J. Brazelton; Johanna Suhonen; Oscar Cavazos; Andrew McCaig; Peter Blum; Natsue Abe; et al. (Geochimica et Cosmochimica Acta, 2025)

Multifaceted Mesodiencephalic Triangles: Insights into Hypertrophic Olivary Degeneration and Oculopalatal Tremor Pathophysiology - Jorge C. Kattah; Kavya Moravineni; Eric Eggenberger; Cody Eggenberger; Aasef G. Shaikh; Rodger J. Elble (The Cerebellum, 2025)
Oculopalatal tremor is a rare neurological disorder characterized by rhythmic oscillations of ocular and palatal muscles. This phenomenon is commonly associated with hypertrophic degeneration of the inferior olive due to loss of GABAergic cerebello-olivary fibers. Oculopalatal tremor highlights the complex interplay between cerebellar, mesodiencephalic, and olivary networks. The principal, medial accessory, and dorsal accessory subnuclei of the inferior olive exhibit rhythmic subthreshold oscillations that are hypothesized to play an important role in oculopalatal tremor. However, delayed tremor onset and variability in hypertrophic olivary degeneration challenge the hypothesis of olivary oscillation as the principal cause of tremorogenesis. A plausible alternative hypothesis is that tremorogenic oscillation emerges from maladaptive cerebellar network plasticity in response to the loss of physiologic climbing fiber activity. The anatomy and physiology of the fastigiobulbar connections are compatible with the clinical characteristics of oculopalatal tremor syndrome, and clinicopathological correlations suggest that the fastigiobulbar pathway is necessary for oculopalatal tremor. Latent brainstem oscillators, released by cerebellar dysfunction, have been proposed but do not explain the anatomical distribution of oscillation. Advanced imaging and computational models have provided insights into possible mechanisms of oscillation but underscore the need for further studies, particularly in a suitable animal model, which does not exist.

P30-23 Boosting Early-Stage ADC Toxicity assessment through human in vitro cell models - B. Recolin; C. Rodger; J. Caruana Santiago; S. Randle; R. Foreman; K. Khan; M. Barbara; J. Kwon; R. Lucey; K. Pryde; M.-Y. Lee; S. Liu; et al. (Toxicology Letters, 2025)

Pinpointing regional unconformities in the Surat Basin, Australia, by statistical identification of neutron wireline log anomalies - C. Andrade; P. M. Vasconcelos; I. Rodger; S. Hörning; J. Esterle (Australian Journal of Earth Sciences, 2025)

Elevated vascular endothelial growth factor a is associated with disruption of default network connectivity in older adults - Arunima Kapoor; Jung Yun Jang; Allison C. Engstrom; Trevor Lohman; Shubir Dutt; John Paul M. Alitin; Isabel J. Sible; Anisa Marshall; Fatemah Shenasa; Aimee Gaubert; Amy Nguyen; David Robert Bradford; et al. (Brain Imaging and Behavior, 2025)
Vascular Endothelial Growth Factor A (VEGF-A) is an angiogenic signaling protein involved in the maintenance of the cerebral vasculature. No prior study has explored whether plasma VEGF-A levels may be associated with brain functional connectivity changes, such as disruption of the default mode network (DMN), which often precedes the development of cognitive changes in aging. Seventy-six independently living older adults (mean age = 70.3 years; SD = 7.5; 31.6% male) free of dementia or clinical stroke underwent venipuncture and brain MRI. Plasma was assayed for VEGF-A. Using resting state functional MRI, region of interest (ROI) to ROI connectivity and graph theory analysis were conducted to determine average connectivity and global efficiency between each of the following ROIs comprising the DMN: medial prefrontal cortex, lateral parietal cortex and precuneus cortex. Multiple linear regression analysis revealed a significant negative association between VEGF-A levels and DMN connectivity (B = − 0.14, 95% CI (-0.26, − 0.01), p =.038), accounting for age, sex, education, and vascular risk factors. Graph theory analysis similarly revealed that VEGF-A levels are associated with global efficiency of the entire network (B = − 0.18, p =.004). These findings suggest that VEGF-A may be elevated early in the progression of neurocognitive disorders. Whether higher levels of VEGF-A contribute to the pathogenesis of neurocognitive disorders or play a protective role in preserving cognitive function warrants further investigation. Clinical Trial Number: N/A; None.

Effects of macro vs. micro initialization and ocean initial-condition memory on the evolution of ensemble spread in the CESM2 large ensemble - Clara Deser; Who M. Kim; Robert C. J. Wills; Isla R. Simpson; Steve Yeager; Gokhan Danabasoglu; Keith Rodgers; Nan Rosenbloom (Climate Dynamics, 2025)
“Single Model initial-condition Large Ensembles” (SMILEs) conducted with Earth system models have transformed our ability to quantify internal climate variability and forced climate change at local and regional scales. An important consideration in their experimental design is the choice of initialization procedure as this influences the duration of initial-condition memory, with implications for interpreting the temporal evolution of both the ensemble-mean and ensemble-spread. Here we leverage the strategic design of the 100-member Community Earth System Model version 2 (CESM2) SMILE to investigate the dependence of ensemble spread on the method of initialization (micro- vs. macro- perturbations) and the effects of ocean initial-condition memory. We find that the evolution of ensemble spread in 10-year low-pass filtered data is relatively insensitive to the method of initialization beyond the second decade, with the notable exception of the tropical Indo-Pacific in the 4th decade, when macro-initialization significantly enhances ensemble spread, possibly as a result of a state-dependent response to major volcanic activity. Initial-condition memory associated with the chosen Atlantic Meridional Overturning Circulation (AMOC) states unfolds in two stages: First, in the North Atlantic lasting 4–5 decades, and subsequently, in the Indo-Pacific sector of the Southern Ocean appearing 35-years after initialization and lasting 3–4 decades. Known AMOC dynamics explain the first stage, but the role of AMOC and the mechanisms responsible for the delayed appearance of initial-condition memory in the Southern Ocean remain to be fully elucidated. Implications and recommendations for the design of future SMILEs are provided.

Stable hydrogen isotope evidence of late-Holocene precipitation variability on the Caribbean slope of the Cordillera Central, Costa Rica - Phyllis Y.Y. Kho; Chad S. Lane; Sally P. Horn; John C. Rodgers; Douglas W. Gamble (Quaternary International, 2024)

P02-16 Modelling chemotherapy-induced peripheral neuropathy on-a-chip - X. Spijkers; G. Avramidou; W. Strijker; E. Nour; M. McFarlane; C. Rodger; J. Harper; L. Masterson; N. Wevers; S. Paternoster (Toxicology Letters, 2024)

Beat-to-beat blood pressure variability, hippocampal atrophy, and memory impairment in older adults - Trevor Lohman; Isabel Sible; Allison C. Engstrom; Arunima Kapoor; Fatemah Shenasa; Elizabeth Head; Lorena Sordo; John Paul M. Alitin; Aimee Gaubert; Amy Nguyen; Kathleen E. Rodgers; David Bradford; et al. (GeroScience, 2024)
Visit-to-visit blood pressure variability (BPV) predicts age-related hippocampal atrophy, neurodegeneration, and memory decline in older adults. Beat-to-beat BPV may represent a more reliable and efficient tool for prospective risk assessment, but it is unknown whether beat-to-beat BPV is similarly associated with hippocampal neurodegeneration, or with plasma markers of neuroaxonal/neuroglial injury. Independently living older adults without a history of dementia, stroke, or other major neurological disorders were recruited from the community ( N = 104; age = 69.5 ± 6.7 (range 55–89); 63% female). Participants underwent continuous blood pressure monitoring, brain MRI, venipuncture, and cognitive testing over two visits. Hippocampal volumes, plasma neurofilament light, and glial fibrillary acidic protein levels were assessed. Beat-to-beat BPV was quantified as systolic blood pressure average real variability during 7-min of supine continuous blood pressure monitoring. The cross-sectional relationship between beat-to-beat BPV and hippocampal volumes, cognitive domain measures, and plasma biomarkers was assessed using multiple linear regression with adjustment for demographic covariates, vascular risk factors, and average systolic blood pressure. Elevated beat-to-beat BPV was associated with decreased left hippocampal volume ( P = .008), increased plasma concentration of glial fibrillary acidic protein ( P = .006), and decreased memory composite score ( P = .02), independent of age, sex, average systolic blood pressure, total intracranial volume, and vascular risk factor burden. In summary, beat-to-beat BPV is independently associated with decreased left hippocampal volume, increased neuroglial injury, and worse memory ability. Findings are consistent with prior studies examining visit-to-visit BPV and suggest beat-to-beat BPV may be a useful marker of hemodynamic brain injury in older adults.

In vitro micropropagation of critically imperiled Crocanthemum canadense (Cistaceae) and identification of endomycorrhizal symbionts - Kendra Sampson; Rodger C. Evans; Robin Browne; Allison K. Walker (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

OS03-09: Modelling Chemotherapy-Induced Peripheral Neuropathy on-a-chip - X. Spijkers; G. Avramidou; W. Strijker; M. McFarlane; C. Rodger; J. Harper; L. Masterson; N. Wevers (Toxicology Letters, 2023)

Modeling genetic benefits and financial costs of integrating biobanking into the conservation breeding of managed marsupials - Lachlan G. Howell; Peter R. Mawson; Pierre Comizzoli; Ryan R. Witt; Richard Frankham; Simon Clulow; Justine K. O'Brien; John Clulow; Paul Marinari; John C. Rodger (Conservation Biology, 2023)
Managed breeding programs are an important tool in marsupial conservation efforts but may be costly and have adverse genetic effects in unavoidably small captive colonies. Biobanking and assisted reproductive technologies (ARTs) could help overcome these challenges, but further demonstration of their potential is required to improve uptake. We used genetic and economic models to examine whether supplementing hypothetical captive populations of dibblers ( Parantechinus apicalis ) and numbats ( Myrmecobius fasciatus ) with biobanked founder sperm through ARTs could reduce inbreeding, lower required colony sizes, and reduce program costs. We also asked practitioners of the black‐footed ferret ( Mustela nigripes ) captive recovery program to complete a questionnaire to examine the resources and model species research pathways required to develop an optimized biobanking protocol in the black‐footed ferret. We used data from this questionnaire to devise similar costed research pathways for Australian marsupials. With biobanking and assisted reproduction, inbreeding was reduced on average by between 80% and 98%, colony sizes were on average 99% smaller, and program costs were 69‐ to 83‐fold lower. Integrating biobanking made long‐standing captive genetic retention targets possible in marsupials (90% source population heterozygosity for a minimum of 100 years) within realistic cost frameworks. Lessons from the use of biobanking technology that contributed to the recovery of the black‐footed ferret include the importance of adequate research funding (US$4.2 million), extensive partnerships that provide access to facilities and equipment, colony animals, appropriate research model species, and professional and technical staff required to address knowledge gaps to deliver an optimized biobanking protocol. Applied research investment of A$133 million across marsupial research pathways could deliver biobanking protocols for 15 of Australia's most at‐risk marsupial species and 7 model species. The technical expertise and ex situ facilities exist to emulate the success of the black‐footed ferret recovery program in threatened marsupials using these research pathways. All that is needed now for significant and cost‐effective conservation gains is greater investment by policy makers in marsupial ARTs.

Prediction of fluid surge in partially-filled clean-bore and transverse baffled tanks of multiple designs under the United Nations Model Regulations - Zhemin Cai; Manudha T. Herath; Luke P. Djukic; Daniel C. Rodgers; Garth M.K. Pearce (Ocean Engineering, 2023)

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Spatial and Temporal Changes in Emergent Marsh and Associated Marsh Birds of the Lower Mobile-Tensaw River Delta in Alabama, USA - Scott A. Rush; John Rodgers; Eric C. Soehren; John A. Trent (Wetlands, 2019)

Assessment of storm surge and structural damage on San Salvador Island, Bahamas, associated with Hurricane Joaquin (2015) - Christopher M. Fuhrmann; Kimberly M. Wood; John C. Rodgers (Natural Hazards, 2019)

Amino acid-linked platinum(II) compounds: non-canonical nucleoside preferences and influence on glycosidic bond stabilities - Bett Kimutai; C. C. He; Andrew Roberts; Marcel L. Jones; Xun Bao; Jun Jiang; Zhihua Yang; M. T. Rodgers; Christine S. Chow (JBIC Journal of Biological Inorganic Chemistry, 2019)

Typha (Cattail) Invasion in North American Wetlands: Biology, Regional Problems, Impacts, Ecosystem Services, and Management - Sheel Bansal; Shane C. Lishawa; Sue Newman; Brian A. Tangen; Douglas Wilcox; Dennis Albert; Michael J. Anteau; Michael J. Chimney; Ryann L. Cressey; Edward DeKeyser; Kenneth J. Elgersma; Sarah A. Finkelstein; et al. (Wetlands, 2019)

Analysis of novel domain-specific mutations in the zebrafish ndr2/cyclops gene generated using CRISPR-Cas9 RNPs - Ashley N. Turner; Reagan S. Andersen; Ivy E. Bookout; Lauren N. Brashear; James C. Davis; David M. Gahan; John P. Gotham; Baraa A. Hijaz; Ashish S. Kaushik; Jordan B. Mcgill; Victoria L. Miller; Zachariah P. Moseley; et al. (Journal of Genetics, 2018)

Detection and genomic characterization of new avian-like hepatitis E virus in a sparrow in the United States - Chenghuai Yang; Leyi Wang; Huigang Shen; Ying Zheng; Phillip C. Gauger; Qi Chen; Jianqiang Zhang; Kyoung-Jin Yoon; Karen M. Harmon; Rodger G. Main; Ganwu Li (Archives of Virology, 2018)

Genomes of ubiquitous marine and hypersaline Hydrogenovibrio , Thiomicrorhabdus and Thiomicrospira spp. encode a diversity of mechanisms to sustain chemolithoautotrophy in heterogeneous environments - Kathleen M. Scott; John Williams; Cody M. B. Porter; Sydney Russel; Tara L. Harmer; John H. Paul; Kirsten M. Antonen; Megan K. Bridges; Gary J. Camper; Christie K. Campla; Leila G. Casella; Eva Chase; et al. (Environmental Microbiology, 2018)
Summary Chemolithoautotrophic bacteria from the genera Hydrogenovibrio, Thiomicrorhabdus and Thiomicrospira are common, sometimes dominant, isolates from sulfidic habitats including hydrothermal vents, soda and salt lakes and marine sediments. Their genome sequences confirm their membership in a deeply branching clade of the Gammaproteobacteria . Several adaptations to heterogeneous habitats are apparent. Their genomes include large numbers of genes for sensing and responding to their environment (EAL‐ and GGDEF‐domain proteins and methyl‐accepting chemotaxis proteins) despite their small sizes (2.1–3.1 Mbp). An array of sulfur‐oxidizing complexes are encoded, likely to facilitate these organisms' use of multiple forms of reduced sulfur as electron donors. Hydrogenase genes are present in some taxa, including group 1d and 2b hydrogenases in Hydrogenovibrio marinus and H. thermophilus MA2‐6, acquired via horizontal gene transfer. In addition to high‐affinity cbb 3 cytochrome c oxidase, some also encode cytochrome bd‐ type quinol oxidase or ba 3 ‐ type cytochrome c oxidase, which could facilitate growth under different oxygen tensions, or maintain redox balance. Carboxysome operons are present in most, with genes downstream encoding transporters from four evolutionarily distinct families, which may act with the carboxysomes to form CO 2 concentrating mechanisms. These adaptations to habitat variability likely contribute to the cosmopolitan distribution of these organisms.

Cold tolerance and invasive potential of the redbay ambrosia beetle (Xyleborus glabratus) in the eastern United States - John P. Formby; John C. Rodgers; Frank H. Koch; Natraj Krishnan; Donald A. Duerr; John J. Riggins (Biological Invasions, 2018)

Microcystin-LR Degradation Following Copper-Based Algaecide Exposures - Ciera M. Kinley; Kyla J. Iwinski-Wood; Tyler D. Geer; Maas Hendrikse; Andrew D. McQueen; Alyssa J. Calomeni; Jenny Liang; Vanessa Friesen; Monique C. Simair; John H. Rodgers (Water, Air, & Soil Pollution, 2018)

Endogenous Sex Steroids Dampen Neuroinflammation and Improve Outcome of Traumatic Brain Injury in Mice - Amy C. Clevenger; Hoon Kim; Ernesto Salcedo; Joan C. Yonchek; Krista M. Rodgers; James E. Orfila; Robert M. Dietz; Nidia Quillinan; Richard J. Traystman; Paco S. Herson (Journal of Molecular Neuroscience, 2018)

Oxidative stress is associated with late‐stage amoebic gill disease in farmed Atlantic salmon ( Salmo salar L.) - M Marcos‐López; C Ruiz Espinosa; H D Rodger; I O'Connor; E MacCarthy; M A Esteban (Journal of Fish Diseases, 2018)

Risk management to prioritise the eradication of new and emerging invasive non-native species - Olaf Booy; Aileen C. Mill; Helen E. Roy; Alice Hiley; Niall Moore; Pete Robertson; Simon Baker; Matt Brazier; Mathilde Bue; Richard Bullock; Steve Campbell; Dominic Eyre; et al. (Biological Invasions, 2017)

Technical pre‐analytical effects on the clinical biochemistry of Atlantic salmon ( Salmo salar L.) - M Braceland; K Houston; A Ashby; C Matthews; H Haining; H Rodger; P D Eckersall (Journal of Fish Diseases, 2017)
Clinical biochemistry has long been utilized in human and veterinary medicine as a vital diagnostic tool, but despite occasional studies showing its usefulness in monitoring health status in Atlantic salmon ( Salmo salar L.), it has not yet been widely utilized within the aquaculture industry. This is due, in part, to a lack of an agreed protocol for collection and processing of blood prior to analysis. Moreover, while the analytical phase of clinical biochemistry is well controlled, there is a growing understanding that technical pre‐analytical variables can influence analyte concentrations or activities. In addition, post‐analytical interpretation of treatment effects is variable in the literature, thus making the true effect of sample treatment hard to evaluate. Therefore, a number of pre‐analytical treatments have been investigated to examine their effect on analyte concentrations and activities. In addition, reference ranges for salmon plasma biochemical analytes have been established to inform veterinary practitioners and the aquaculture industry of the importance of clinical biochemistry in health and disease monitoring. Furthermore, a standardized protocol for blood collection has been proposed.

Pedelecs as a physically active transportation mode - James E. Peterman; Kalee L. Morris; Rodger Kram; William C. Byrnes (European Journal of Applied Physiology, 2016)

Genomic comparison of virulent and non‐virulent S treptococcus agalactiae in fish - C M J Delannoy; R N Zadoks; M Crumlish; D Rodgers; F A Lainson; H W Ferguson; J Turnbull; M C Fontaine (Journal of Fish Diseases, 2016)
Streptococcus agalactiae infections in fish are predominantly caused by beta‐haemolytic strains of clonal complex ( CC ) 7, notably its namesake sequence type ( ST ) 7, or by non‐haemolytic strains of CC 552, including the globally distributed ST 260. In contrast, CC 23, including its namesake ST 23, has been associated with a wide homeothermic and poikilothermic host range, but never with fish. The aim of this study was to determine whether ST 23 is virulent in fish and to identify genomic markers of fish adaptation of S . agalactiae . Intraperitoneal challenge of Nile tilapia, O reochromis niloticus ( L innaeus), showed that ST 260 is lethal at doses down to 10 2 cfu per fish, whereas ST 23 does not cause disease at 10 7 cfu per fish. Comparison of the genome sequence of ST 260 and ST 23 with those of strains derived from fish, cattle and humans revealed the presence of genomic elements that are unique to subpopulations of S . agalactiae that have the ability to infect fish ( CC 7 and CC 552). These loci occurred in clusters exhibiting typical signatures of mobile genetic elements. PCR ‐based screening of a collection of isolates from multiple host species confirmed the association of selected genes with fish‐derived strains. Several fish‐associated genes encode proteins that potentially provide fitness in the aquatic environment.

Erratum to: The chronic effects of an extract of Bacopa monniera (Brahmi) on cognitive function in healthy human subjects - C. Stough; J. Lloyd; J. Clarke; L. A. Downey; C. W. Hutchison; T. Rodgers; P. J. Nathan (Psychopharmacology, 2015)

The effect of impedance to root growth on plant architecture in wheat - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Andrew L. Phillips; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Canopy interactions and physical stress gradients in subtidal communities - Scott Bennett; Thomas Wernberg; Thibaut de Bettignies; Gary A. Kendrick; Robert J. Anderson; John J. Bolton; Kirsten L. Rodgers; Nick T. Shears; Jean‐Charles Leclerc; Laurent Lévêque; Dominique Davoult; Hartvig C. Christie (Ecology Letters, 2015)
Species interactions are integral drivers of community structure and can change from competitive to facilitative with increasing environmental stress. In subtidal marine ecosystems, however, interactions along physical stress gradients have seldom been tested. We observed seaweed canopy interactions across depth and latitudinal gradients to test whether light and temperature stress structured interaction patterns. We also quantified interspecific and intraspecific interactions among nine subtidal canopy seaweed species across three continents to examine the general nature of interactions in subtidal systems under low consumer pressure. We reveal that positive and neutral interactions are widespread throughout global seaweed communities and the nature of interactions can change from competitive to facilitative with increasing light stress in shallow marine systems. These findings provide support for the stress gradient hypothesis within subtidal seaweed communities and highlight the importance of canopy interactions for the maintenance of subtidal marine habitats experiencing environmental stress.

Global low-frequency motions in protein allostery: CAP as a model system - Philip D. Townsend; Thomas L. Rodgers; Ehmke Pohl; Mark R. Wilson; Tom C. B. McLeish; Martin J. Cann (Biophysical Reviews, 2015)

Wheat root growth responses to horizontal stratification of fertiliser in a water-limited environment - Kemo Jin; Jianbo Shen; Rhys W. Ashton; Rodger P. White; Ian C. Dodd; Martin A. J. Parry; William R. Whalley (Plant and Soil, 2015)

Differential characterization of emerging skin diseases of rainbow trout – a standardized approach to capturing disease characteristics and development of case definitions - B Oidtmann; S E LaPatra; D Verner‐Jeffreys; M Pond; E J Peeler; P A Noguera; D W Bruno; S St‐Hilaire; C B Schubiger; K Snekvik; M Crumlish; D M Green; et al. (Journal of Fish Diseases, 2013)
Farmed and wild salmonids are affected by a variety of skin conditions, some of which have significant economic and welfare implications. In many cases, the causes are not well understood, and one example is cold water strawberry disease of rainbow trout, also called red mark syndrome, which has been recorded in the UK since 2003. To date, there are no internationally agreed methods for describing these conditions, which has caused confusion for farmers and health professionals, who are often unclear as to whether they are dealing with a new or a previously described condition. This has resulted, inevitably, in delays to both accurate diagnosis and effective treatment regimes. Here, we provide a standardized methodology for the description of skin conditions of rainbow trout of uncertain aetiology. We demonstrate how the approach can be used to develop case definitions, using coldwater strawberry disease as an example.

Co‐Infection with Pseudomonas anguilliseptica and Delftia acidovorans in the European eel, Anguilla anguilla (L.): a case history of an illegally trafficked protected species - K B Andree; C J Rodgers; D Furones; E Gisbert (Journal of Fish Diseases, 2013)
Inspections by customs agents at Barcelona airport discovered 420 kg of contraband glass eels prepared for shipment to Hong Kong. After confiscation of these animals by police, they were transported to holding facilities to be maintained until after a judicial hearing. Upon arrival, they were separated into two groups and held under ambient flow‐through conditions in fresh water. During their captivity period, several peaks in mortality occurred and multiple bacterial strains were isolated from moribund animals. Sequencing of 16S rDNA was used to determine specific identity of the isolates. An initial isolation of Pseudomonas anguilliseptica was treated with oxytetracycline. A subsequent isolation of Delftia acidovorans proved resistant to oxytetracycline and was treated with gentamicin in combination with sulphadiazine–trimethoprim. Once the health condition of the animals was stabilized, they were partitioned into groups and subsequently released as part of a restocking effort for the species following the guidelines of Regulation (EC) 1100/2007 (Anon 2007). This represents the first record for both bacterial species in the host Anguilla anguilla in the Spanish Mediterranean.

Temporal guidance of musicians’ performance movement is an acquired skill - M. W. M. Rodger; S. O’Modhrain; C. M. Craig (Experimental Brain Research, 2013)

Factors affecting the increased energy expenditure during passive cycling - James E. Peterman; Rodger Kram; William C. Byrnes (European Journal of Applied Physiology, 2012)

Carbon dynamics in a 60 year fallowed loamy-sand soil compared to that in a 60 year permanent arable or permanent grassland UK soil - Yuping Wu; Sarah Kemmitt; Rodger P. White; Jianming Xu; Philip C. Brookes (Plant and Soil, 2012)

Is photocleavage of DNA by YOYO-1 using a synchrotron radiation light source sequence dependent? - Emma L. Gilroy; Søren Vrønning Hoffmann; Nykola C. Jones; Alison Rodger (European Biophysics Journal, 2011)

Epitheliocystis in Atlantic salmon, Salmo salar L., farmed in fresh water in Ireland is associated with ‘ Candidatus Clavochlamydia salmonicola’ infection - S O Mitchell; T Steinum; H Rodger; C Holland; K Falk; D J Colquhoun (Journal of Fish Diseases, 2010)
Intracellular inclusions containing chlamydia‐like organisms are frequently observed in the gill epithelial cells of Atlantic salmon, Salmo salar L., cultured in fresh water in Ireland. In this study, the causative agent was identified in four separate freshwater sites, using 16s rRNA sequencing, as ‘ Candidatus Clavochlamydia salmonicola’. Histopathology and real‐time (RT) PCR were used to further assess infections. The prevalence of infection ranged from 75–100% between sites and infection intensity was highly variable. No significant lesions were associated with these infections. As a diagnostic tool, RT‐PCR proved marginally more sensitive than histopathology. The fate of ‘ Candidatus Clavochlamydia salmonicola’ in Atlantic salmon post‐seawater transfer was investigated in a 12‐week marine longitudinal study. Both RT‐PCR and histopathological examination indicate that the organism disappears from the gills 4–6 weeks post‐transfer.

Prospective longitudinal studies of salmonid alphavirus infections on two Atlantic salmon farms in Ireland; evidence for viral persistence - D A Graham; E Fringuelli; C Wilson; H M Rowley; A Brown; H Rodger; M F McLoughlin; C McManus; E Casey; L J McCarthy; N M Ruane (Journal of Fish Diseases, 2010)
Prospective longitudinal studies of two outbreaks of pancreas disease in Atlantic salmon (AS), Salmo salar L., in Ireland were conducted. Both outbreaks occurred during the marine phase of production, with one caused by salmonid alphavirus subtype 1 (SAV1) and the other by SAV4. In addition to screening a range of tissues by real‐time reverse transcriptase polymerase chain reaction (RRT‐PCR), virological, serological and histopathological examinations were performed along with partial genome sequencing and results were related to environmental and production data and farm history. On Farm 1 (marine sampling only), infection was detected within 3 weeks of smolts being placed on the farm, while on Farm 2 (freshwater and marine sampling), infection was first detected 315 days after transfer to sea. In both outbreaks, RRT‐PCR signals were detected in a range of tissues including gill, heart, kidney, pancreas/pyloric caeca, brain and serum. Persistence of signal was longest in gill and heart (≥265 days on both farms) and shortest in serum. Mortalities on the two farms varied from 10.9% to 30%. In both cases, partial genome sequence of the causative viruses were identical to SAV strains detected in previous populations of AS on each of the study farms, including populations with which the study populations overlapped in time and space.

Intact amino acid uptake by northern hardwood and conifer trees - Anne Gallet-Budynek; Edward Brzostek; Vikki L. Rodgers; Jennifer M. Talbot; Sharon Hyzy; Adrien C. Finzi (Oecologia, 2009)

The Impact of Hurricane Katrina on the Coastal Vegetation of the Weeks Bay Reserve, Alabama from NDVI Data - John C. Rodgers; Adam W. Murrah; William H. Cooke (Estuaries and Coasts, 2009)

Ruthenium polypyridyl complexes and their modes of interaction with DNA: Is there a correlation between these interactions and the antitumor activity of the compounds? - Eva Corral; Anna C. G. Hotze; Hans den Dulk; Anna Leczkowska; Alison Rodger; Michael J. Hannon; Jan Reedijk (JBIC Journal of Biological Inorganic Chemistry, 2009)

Phylogenetic analyses and molecular epidemiology of European salmonid alphaviruses (SAV) based on partial E2 and nsP3 gene nucleotide sequences - E Fringuelli; H M Rowley; J C Wilson; R Hunter; H Rodger; D A Graham (Journal of Fish Diseases, 2008)
Sequence data were generated for portions of the E2 and nsP3 genes of 48 salmonid alphaviruses from farmed Atlantic salmon (AS), Salmo salar L . , and rainbow trout (RT), Oncorhynchus mykiss (Walbaum), in marine and freshwater environments, respectively, from the Republic of Ireland, Northern Ireland, England, Scotland, Norway, France, Italy and Spain between 1991 and 2007. Based on these sequences, and those of six previously published reference strains, phylogenetic trees were constructed using the parsimony method. Trees generated with both gene segments were similar. Clades corresponding to the three previously recognized subtypes were generated and in addition, two further new clades of viruses were identified. A single further strain (F96‐1045) was found to be distinct from all of the other strains in the study. The percentage of nucleotide divergence within clades was generally low (0–4.8% for E2, 0–6.6% for nsP3). Interclade divergence tended to be higher (3.4–19.7% for E2, 6.5–28.1% for nsP3). Based on these results and using current SAV terminology, the two new clades and F96‐1045 were termed SAV subtypes 4, 5 and 6, respectively. SAV4 contained AS strains from Ireland and Scotland, while SAV5 contained only Scottish AS strains. Recently identified SAV strains from RT in Italy and Spain were shown to belong to SAV2. In addition, marine AS strains belonging to SAV2 were identified for the first time. Analysis of the origin of several clusters of strains with identical E2 and nsP3 sequences strongly support horizontal transmission of virus between farms and aquaculture companies. Evidence in support of vertical transmission was not found.

The invasive species Alliaria petiolata (garlic mustard) increases soil nutrient availability in northern hardwood-conifer forests - Vikki L. Rodgers; Benjamin E. Wolfe; Leland K. Werden; Adrien C. Finzi (Oecologia, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The sensitivity of tree growth to air mass variability and the Pacific Decadal Oscillation in coastal Alabama - Jason C. Senkbeil; John C. Rodgers; Scott C. Sheridan (International Journal of Biometeorology, 2007)

Improving fluorometry as a source tracking method to detect human fecal contamination - Peter G. Hartel; Jennifer L. McDonald; Lisa C. Gentit; Sarah N. J. Hemmings; Karen Rodgers; Katy A. Smith; Carolyn N. Belcher; Robin L. Kuntz; Yaritza Rivera-Torres; Ernesto Otero; Eduardo C. Schröder (Estuaries and Coasts, 2007)

Atypical anxiolytic-like response to naloxone in benzodiazepine-resistant 129S2/SvHsd mice: role of opioid receptor subtypes - R. J. Rodgers; R. Augar; N. Berryman; C. J. Hansom; M. L. O’Mahony; R. M. Palmer; A. Stevens; A. J. Tallett (Psychopharmacology, 2006)

Graded ephrin-A2 expression in the developing hamster superior colliculus - Sherralee S. Lukehurst; Carolyn E. King; Lyn D. Beazley; David K. C. Tay; Kwok-Fai So; Jennifer Rodger (Experimental Brain Research, 2006)

Interannual-to-decadal variability of North Atlantic air-sea CO 2 fluxes - S. Raynaud; J. C. Orr; O. Aumont; K. B. Rodgers; P. Yiou (Ocean Science, 2006)
The magnitude of the interannual variability of North Atlantic air-sea CO2 fluxes remains uncertain. Interannual extremes simulated by atmospheric inverse approaches are typically about ±0.3 Pg C yr−1, whereas those from ocean models are less than ±0.1 Pg C yr−1. Thus variability in the North Atlantic is either about 60% or less than 20% of the global variability of about ±0.5 Pg C yr−1 (as estimated by both approaches). Here we explore spatiotemporal variability within the North Atlantic basin of one ocean model in order to more fully describe potential counteracting trends in different regions that may explain why basin-wide variability is small relative to global-scale variability. Typical atmospheric inverse approaches separate the North Atlantic into at most a few regions and thus cannot properly simulate such counteracting effects. For this study, two simulations were made with a biogeochemical model coupled to a global ocean general circulation model (OGCM), which itself was forced by 55-year NCEP reanalysis fields. In the first simulation, atmospheric CO2 was maintained at the preindustrial level (278 ppmv); in the second simulation, atmospheric CO2 followed the observed increase. Simulated air-sea CO2 fluxes and associated variables were then analysed with a statistical tool known as multichannel singular spectrum analysis (MSSA). We found that the subtropical gyre is not the largest contributor to the overall, basin-wide variability, in contrast to previous suggestions. The subpolar gyre and the inter-gyre region (the transition area between subpolar and subtropical gyres) also contribute with multipolar anomalies at multiple frequencies: these tend to cancel one another in terms of the basin-wide air-sea CO2 flux. We found a strong correlation between the air-sea CO2 fluxes and the North Atlantic Oscillation (NAO), but only if one takes into account time lags as does MSSA (maximum r=0.64 for lags between 1 and 3 years). The effect of increasing atmospheric CO2 (the anthropogenic perturbation) on total variability was negligible at interannual time scales, whereas at the decadal (13-year) time scale, it increased variability by 30%.

Feeding responses to selected alkaloids by gypsy moth larvae, Lymantria dispar (L.) - Vonnie D. C. Shields; Erin J. Rodgers; Nicole S. Arnold; Denise Williams (The Science of Nature, 2006)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

A model for wave control on coral breakage and species distribution in the Hawaiian Islands - C. D. Storlazzi; E. K. Brown; M. E. Field; K. Rodgers; P. L. Jokiel (Coral Reefs, 2005)

The reality of psychomotor problems, and the possibility of Parkinson?s disorder, in some recreational ecstasy/MDMA users: a rejoinder to Sumnall et al. (2003) - A. C. Parrott; J. Rodgers; T. Buchanan; A. B. Scholey; T. Heffernan; J. Ling (Psychopharmacology, 2004)

Cotton rat Sihi- M3 is a minimally oligomorphic Mhc I-b molecule that binds the chemotactic peptide fMLF under stringent conditions - C. Kuyler Doyle; Richard G. Cook; Robert R. Rich; John R. Rodgers (Immunogenetics, 2003)

Algicidal Effectiveness of Clearigate, Cutrine-Plus, and Copper Sulfate and Margins of Safety Associated with Their Use - C. L. Murray-Gulde; J. E. Heatley; A. L. Schwartzman; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 2002)

Insulin-like effects of a physiologic concentration of carnitine on cardiac metabolism - Robert L. Rodgers; Michael E. Christe; George C. Tremblay; John R. Babson; Thomas Daniels (Molecular and Cellular Biochemistry, 2001)

Effect of a freeze-dried CMC/PLGA microsphere matrix of rhBMP-2 on bone healing - Jay A. Schrier; Betsy F. Fink; Janet B. Rodgers; Henry C. Vasconez; Patrick P. DeLuca (AAPS PharmSciTech, 2001)

The chronic effects of an extract of Bacopa monniera (Brahmi) on cognitive function in healthy human subjects - Stough C.; Nathan P.; Lloyd J.; Clarke J.; Hutchison C.; Downey L.; Rodgers T. (Psychopharmacology, 2001)

Early ontogeny of coal grunter from hormone‐induced spawnings and laboratory‐reared embryos and larvae - P. G. Close; C. G. Barlow; L. J. Rodgers (Journal of Fish Biology, 2001)
Spawning of coal grunter Hephaestus carbo was successfully induced using doses of human chorionic gonadotrophin (hCG) between 500 and 3000 IU kg (body weight) −1 . Water hardened eggs are telolecithal, amber in colour, spherical, transparent, demersal and slightly adhesive with a single large oil droplet and perivitelline space 47% of total egg volume. Cleavage begins 10–15 min after fertilization. Epiboly begins 6h after fertilization and continues for 4 h. Invagination of the neural tube is apparent 11·5 h after fertilization, followed by progressive organogenesis up to hatching 60–80 h after fertilization. An invagination in the yolk, consistent in shape, position and time of appearance among embryos spawned from numerous brood stock pairs, was visible in all fertilized eggs between neurulation (11‐5 h) and early organogenesis (20 h). The functional significance of this yolk invagination is unknown. Newly‐hatched larvae (4·2 mm L T ) are elongate and possess well developed eyes, a functional mouth, and a large yolk sac. Yolk is fully resorbed and first feeding occurs at 6 days posthatching. The sequence of fin formation is caudal, second dorsal and anal, first dorsal, pectoral and pelvic. The prefiexion larval stage lasts for c. 8 days and flexion of the notochord is complete within a further 8–9 days. Squamation commences at 30 days posthatching and transition to the juvenile life stage is complete by 35–40 days posthatching.

Effects of a Homologous Series of Linear Alcohol Ethoxylate Surfactants on Fathead Minnow Early Life Stages - R. E. Lizotte Jr.; D. C. L. Wong; P. B. Dorn; J. H. Rodgers Jr. (Archives of Environmental Contamination and Toxicology, 1999)

Comparative Toxicity of Chlordane, Chlorpyrifos, and Aldicarb to Four Aquatic Testing Organisms - M. T. Moore; D. B. Huggett; W. B. Gillespie Jr.; J. H. Rodgers Jr.; C. M. Cooper (Archives of Environmental Contamination and Toxicology, 1998)

Experimental Factors That May Affect Toxicity of Cadmium to Freshwater Organisms - B. C. Suedel; J. H. Rodgers Jr.; E. Deaver (Archives of Environmental Contamination and Toxicology, 1997)

Comparative Aqueous Toxicity of Silver Compounds: Laboratory Studies with Freshwater Species - J. H. Rodgers, Jr.; E. Deaver; B. C. Suedel; P. L. Rogers (Bulletin of Environmental Contamination and Toxicology, 1997)

Formulated sediment as a reference and dilution sediment in definitive toxicity tests - B. C. Suedel; E. Deaver; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 1996)

Experimental factors that may affect toxicity of aqueous and sediment-bound copper to freshwater organisms - B. C. Suedel; E. Deaver; J. H. Rodgers (Archives of Environmental Contamination and Toxicology, 1996)

Formulated Sediment as a Reference and Dilution Sediment in Definitive Toxicity Tests - B. C. Suedel; E. Deaver; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 1996)

Experimental Factors That May Affect Toxicity of Aqueous and Sediment-Bound Copper to Freshwater Organisms - B. C. Suedel; E. Deaver; J. H. Rodgers, Jr. (Archives of Environmental Contamination and Toxicology, 1996)

Multiple drug resistance inAerobacter aerogenes - P. G. Bolion; A. C. R. Dean; P. J. Rodgers (Antonie van Leeuwenhoek, 1967)